Fermentasi Diam dan Goyang Isolat Kapang Endofit dari Brucea javanica L. Merr. dan Uji Aktivitas Antimikroba - Shirly Kumala; Wibowo Mangunwardoyo; Peny Budiarti (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Exploring an antibiotic from microorganism is potential to discover the new antibiotic. The endophytic microorganism is one of the minimanufacturer producing the secondary metabolite such as antibiotic. Screening on the endophytic molds isolated from Brucea javanica L. Merr has been carried out. Fermentation in still and shake culture were used to produce the antibiotic using PDY medium. Antimicrobial activity was assayed using diffusion agar method. The results revealed that shake culture gave a better antimicrobial activity than still culture. Amount of eight isolate studied showed microbial activity against Gram positive bacteria: Staphylococcus aureus and Bacillus subtilis also Gram Negative bacteria: Escherichia coli and Salmonella typhi, however no microbial activity recorded againts Candida albicans. Isolate number 1.2 gave the highest antimicrobial activity on still culture and isolate number 1.7 gave the highest antimicrobial activity on shake culture. Further research should be carried out on identification and purification of the antimicrobial agent.